2016
DOI: 10.1038/srep33962
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of trichothecene mycotoxins of Fusarium oxysporum by ferulic acid aggravates oxidative damage in Rehmannia glutinosa Libosch

Abstract: Rehmannia glutinosa is an important medicinal herb that cannot be replanted in the same field due to the effects of autotoxic substances. The effects of these substances on R. glutinosa in continuous cropping systems are unknown. In the present study, bioassays revealed that R. glutinosa exhibited severe growth restriction and higher disease indices in the FO+FA (F.oxysporum pretreated with ferulic acid) treatment. The increases in the contents of MDA and H2O2 were greater in the FA+FO treatment than in the FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Various studies indicated that consecutive monoculture of medicinal plants led to the accumulation of toxic compounds in soil, such as microbial secondary metabolites, autotoxins released by plant roots, and so on [43,44,45]. In this study, it was found that the percentage of reads categorized to penicillin and cephalosporin biosynthesis (ko00311) was significantly higher in CM than in NP (Figure S9).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Various studies indicated that consecutive monoculture of medicinal plants led to the accumulation of toxic compounds in soil, such as microbial secondary metabolites, autotoxins released by plant roots, and so on [43,44,45]. In this study, it was found that the percentage of reads categorized to penicillin and cephalosporin biosynthesis (ko00311) was significantly higher in CM than in NP (Figure S9).…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, the metagenomics analysis showed that the levels of the clusters of defense mechanisms (i.e., antibiotic resistance, ABC transporters, efflux transporter) and DNA repair were higher in CM than in NP for harmful/indicator microorganisms ( Figures S12 and S14 ), which might confer them high tolerance levels to toxic or antimicrobial compounds [ 41 , 42 ]. Various studies indicated that consecutive monoculture of medicinal plants led to the accumulation of toxic compounds in soil, such as microbial secondary metabolites, autotoxins released by plant roots, and so on [ 43 , 44 , 45 ]. In this study, it was found that the percentage of reads categorized to penicillin and cephalosporin biosynthesis (ko00311) was significantly higher in CM than in NP ( Figure S9 ).…”
Section: Discussionmentioning
confidence: 99%
“…while inhibiting growth of the beneficial Pseudomonas strain ( Wu et al, 2015 ). Bioassay showed that high concentration of phenolic acids were not only phytotoxic to R. glutinosa seedlings but also enhanced the oxidative damage and outbreak of wilting symptom in R. glutinosa together with F. oxysporum ( Li et al, 2012 , 2016 ). These findings suggested that extended monoculture of R. glutinosa altered the soil microbial community through the presence of phenolic acids in root exudates, resulting in the decline of beneficial bacteria with antagonistic activity against pathogens and the explosive growth and proliferation of F. oxysporum .…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that extended monoculture of R. glutinosa altered the soil microbial community through the presence of phenolic acids in root exudates, resulting in the decline of beneficial bacteria with antagonistic activity against pathogens and the explosive growth and proliferation of F. oxysporum . Potentially, the phytotoxicity of accumulated phenolic acids together with the pathogenicity of proliferating associated phytopathogens were reported as potentially responsible for the replant problems/diseases of R. glutinosa ( Wu et al, 2015 , 2018a ; Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Shu Dihuang is usually applied to in the traditional Chinese medicine formulas that can nourish the Yin deficiency of liver, kidney and heart [1][2][3]. Many clinical and experimental studies have reported that the root of R. glutinosa possesses hypoglycaemic [4], anti-oxidant [5,6] anti-cancer [7], anti-inflammatory [8], and immuneenhancement effects [9].…”
Section: Introductionmentioning
confidence: 99%